Effects of L-methionine-DL-Sulphoximine(MSO) and 3-(3,4-dichlorophenyl)- N-N-dimethylurea(DCMU) on Physiological Activity of Cyanobacteria Nostoc species Isolated from Lichen Peltigeracanina - Jabbar F- Al-maadhidi (Journal of Madenat Alelem University College, 2016)
Lichen is a Symbiotic system consist of nitrogen fixing Cyanobacteria or and algae and fungus. Cyanobacteria can fix nitrogen in a peculiar differentiated cells called heterocyst under aerobic conditions, those heterocyst are the loci of nitrogenase activity. The organic nitrogen and carbohydrates produced by cyanobacteria utilized by fungi and the fungus supplying the cyanobacteria and algae by inorganic metals coming from dissolved rocks by acids produced by fungi. Culture of Nostocspp treated with MOS excreted, the newly fixed nitrogen in form of ammonia into liquid media, which is proportions with the concentration of the analog and detected after 6 h of treatment. Acetylene reduction technique (nitrogenase activity) was not affected by analog (MSO) treatment. The growth of Cyanobacteria Nostocspp was slightly inhibited starting after 6 h of treatment. The rates of carbon fixation were highly enhanced after treatment leading to increase the number of (PGBS) in the Cyanobacteria cells. The combination treatment of Nostocspp culture by MSO and DCMU showed the following: carbon and nitrogen fixation are dependent of each other, slight inhibitions in culture growth, 50% inhibition in ammonia release, complete inhibition of carbon fixation and disappeared of extra PGB. Light intensities and carbon fixation are dependent even in the presence of MSO. The cultivation of Nostocspp culture under Ar/O2/CO2 in presence of MSO gives reverse relationship between the cellular incorporated carbon and time. Electron micrograph showed an increase in PGBs of the lichen P. conina treated with MSO through the first hour of treatment and then disappeared after 24 h.